Review of advances in molecular structure and biological function of alpha toxin of Clostridium perfringens - Xu, Chongli; She, Yuhan; Fu, Fengyang; Xu, Chongbo; Peng, Kun (Canadian journal of veterinary research, 2024)
alpha toxin has become the subject of research in recent years. The objective of this article was to review and summarize recent research on the molecular structure and biological function of the alpha toxin of Clostridium perfringens. This includes the work of our research team, as well as that of other researchers. Clostridium perfringens is an anaerobic, spore-forming, Gram-positive bacillus. It can cause various intestinal diseases, such as gas gangrene, food poisoning, non-foodborne diarrhea, and enteritis. Clostridium perfringens can be classified into 5 toxinotypes A, B, C, D, and E, based on the production of major toxins. Each type of C. perfringens produces alpha toxin, which is one of the most important lethal and dermonecrotic toxins and is considered a primary virulence factor. alpha toxin is a multifunctional metalloenzyme with phospholipase C and sphingomyelinase activities that simultaneously hydrolyze phosphatidylcholine and sphingomyelin. It can therefore destroy the integrity of cell membranes and eventually cause cell lysis. The clinical effects of alpha toxins are characterized by cytotoxicity, hemolytic activity, lethality, skin necrosis, platelet aggregation, and increased vascular permeability. Future research will concentrate on the pathogenesis of alpha toxin exposure, clarifying the interaction between alpha toxin and the cell membrane and investigating the mechanism of activating platelet function. This research will have substantial theoretical and practical value in controlling disease progression, identifying targeted therapeutic sites, and reducing the toxic effects of vaccines.